Enhanced Thermal Stability of Halide Perovskite CsPbX3 Nanocrystals by a Facile TPU Encapsulation. Issue 4 (5th December 2019) - Shi, Jindou; Ge, Wanyin; Gao, Wenxing; Xu, Meimei; Zhu, Jianfeng; Li, Yongxiang
Abstract: Improving the stability of all‐inorganic halide perovskite nanocrystals has become an urgent task that cannot be ignored in practical applications. Lead halide perovskite CsPbX3 (X = Br, I, Cl) compounds are considered as the potential materials for next‐generation light‐emitting devices due to their superior optical properties. However, they are threatened by thermal degradation and atmospheric moisture. In order to better solve this practical problem, CsPbBr3 quantum dots (QDs) and CsPbBr3 @Cs4 PbBr6 nanocrystals (NCs) are tested under heating and cooling cycles, and the photoluminescence (PL) intensity loss of different perovskite materials at high temperatures is investigated. In addition, a thermoplastic polyurethane encapsulation strategy is proposed to improve their properties of thermal degradation and moisture resistance. This inexpensive and convenient method not only greatly reduces the PL intensity loss, but also shows excellent PL performance even in water. The encapsulated material has both flexible and elastic properties, which paves the way for the next commercial processing of all inorganic perovskite materials. Abstract : A thermoplastic polyurethane encapsulating strategy is presented to reduce the photoluminescence loss of perovskite CsPbX3 under higher temperature condition and to prolong its storage stability in water. The encapsulated CsPbX3 film exhibits excellent mechanical properties (flexibility and elasticity). This will pave the way for the next commercial processing of all inorganic perovskite materials.